West Bank and Gaza Poverty and Shared Prosperity Diagnostic 2011-2017 - Atamanov, Aziz (World Bank, Washington, DC, 2018)
This poverty diagnostic documents changes in welfare and living standards in the West Bank and Gaza over the period 2011 to 2017. Since the last poverty assessment for these territories, in 2011, the economic constraints facing them have worsened. The 2011 poverty assessment covered the period from 2004 to 2009, spanning the end of the second Intifada, as well as the 2007 internal divide in Gaza. The current diagnostic draws on the 2011 and 2017 Palestinian expenditure and consumption surveys (PECS) to assess key welfare trends and highlight areas for further investigation. The principal goal of this is to be timely and actionable, given the worsening outlook in the territories and the urgency of an effective response.